Assistance for Improving Household Welfare in Labuhan Deli District through Strengthening Income, Education, and Health Aspects - Muammar Rinaldi; Indra Maipita; Eko Wahyu Nugrahadi (Outline Journal of Community Development, 2026)
This community service activity aims to improve household welfare in Labuhan Deli District by strengthening the aspects of income, education, and health. The program was implemented to increase community awareness and capacity in managing household economic activities, supporting educational development, and promoting healthy living practices among family members. The target participants of this activity were households categorized as economically vulnerable in the community. The methods used in this program included socialization, training, counseling, and community mentoring. These activities were conducted through a participatory approach involving group discussions, educational sessions, and practical guidance related to household financial management, the importance of education for children, and basic health practices such as hygiene and preventive care. In addition, monitoring and evaluation were carried out to observe changes in knowledge and behavior among participants after the implementation of the program. The results show that participants experienced increased understanding of household income management, improved awareness of the importance of education, and better knowledge of maintaining family health. Participants also demonstrated positive responses and active participation during the mentoring sessions. In conclusion, the assistance program contributed positively to strengthening the economic, educational, and health capacities of households, thereby supporting sustainable improvements in community welfare.